Programming Languages and Systems 29th European Symposium on Programming, ESOP 2020, Held as Part of the European Joint Conferences on Theory and Practice of Software, ETAPS 2020, Dublin, Ireland, April 25-30, 2020, Proceedings - Müller, Peter (Theoretical Computer Science and General Issues,, 2020)
This open access book constitutes the proceedings of the 29th European Symposium on Programming, ESOP 2020, which took place in Dublin, Ireland, in April 2020, and was held as Part of the European Joint Conferences on Theory and Practice of Software, ETAPS 2020. The papers deal with fundamental issues in the specification, design, analysis, and implementation of programming languages and systems. .